2022
DOI: 10.1016/j.crphar.2021.100072
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for drug repurposing against coronavirus targets

Abstract: Repurposing regulatory agency approved drugs and investigational compounds with known safety profiles can significantly fast track the drug development timeline over de novo drug discovery, with lower investment requirements and improved attrition rate. These advantages are vital in any epidemic or pandemic situation, where hospital beds are occupied by patients for whom there is no known treatment. Here we examine drug repurposing in the context of human coronaviruses, SARS-CoV, MERS-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…In line with the different strategies for drug repurposing to target virus replication and disease/complications ( Sultana et al, 2020 ; Smith et al, 2022 ), we have previously hypothesized that p53 activator Nutlin-3, a potent and selective activator of p53 might be useful to counteract SARS-CoV-2 infection ( Zauli et al, 2020 ). Besides natural compounds with anti-inflammatory activity, other studies have directly suggested that pharmacological activation of p53 might be a strategy to counteract SARS-CoV-2 infection ( Ramaiah, 2020 ; Zauli et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with the different strategies for drug repurposing to target virus replication and disease/complications ( Sultana et al, 2020 ; Smith et al, 2022 ), we have previously hypothesized that p53 activator Nutlin-3, a potent and selective activator of p53 might be useful to counteract SARS-CoV-2 infection ( Zauli et al, 2020 ). Besides natural compounds with anti-inflammatory activity, other studies have directly suggested that pharmacological activation of p53 might be a strategy to counteract SARS-CoV-2 infection ( Ramaiah, 2020 ; Zauli et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…An indole derivative umifenovir (Arbidol, ethyl 6-bromo-4-[(dimethylamino)methyl]-5-hydroxy-1-methyl-2-[(phenylsulfanyl)methyl]-1H-indole-3-carboxylate) is widely used drug for the prevention and treatment of COVID-19 and some other viral infections [2,9,30]. We have studied electrochemical behavior of Umi on the screen-printed electrodes modified with single-wall carbon nanotubes.…”
Section: Electrochemical Behavior Of Umi On Spe/swcntmentioning
confidence: 99%
“…used drug for the prevention and treatment of COVID-19 and some other viral infections [2,9,30]. We have studied electrochemical behavior of Umi on the screen-printed electrodes modified with single-wall carbon nanotubes.…”
Section: Electrochemical Behavior Of Umi On Spe/swcntmentioning
confidence: 99%
“…Main protease (Mpro or 3CLpro) and papain-like protease (PLpro) are viral proteases that are required for the replication of SARS-CoV-2. However, targeting these crucial steps by lopinavir/ritonavir and darunavir/cobicistat did not provide convincing clinical benefit in patients with COVID-19 [ 200 ]. In contrast, nirmatrelvir, an orally-administered C3-like protease inhibitor that is sold in combination with ritonavir under the brand name Paxlovid, is recommended for use in high-risk, non-hospitalized COVID-19 patients from the age of 12 within five days after symptoms onset.…”
Section: Antiviral and Immunomodulatory Treatments For Covid-19mentioning
confidence: 99%